Sino-Russian Cooperation in the Yangtze and Volga River Basins - Juntao Wang; D. E. Lyubina (Евразийская интеграция: экономика, право, политика)
Cooperation between the regions of the Volga Federal District and the territories of the upper and middle reaches of the Yangtze River of the People’s Republic of China is one of the tools for activating multifaceted Russian-Chinese relations. The creation of a Sino-Russian cooperation mechanism through the Volga — Yangtze Format is of great importance for promoting the development of economic and trade exchanges between the two states, as well as the formation of points of contact in the humanitarian sphere. The similarity of geographical features of these regions is a good basis for the exchange of experience in solving economic, environmental and humanitarian problems of the development of territories located along major waterways.Aim. The purpose of the work is to identify the main vectors of possible development of cooperation and ways to overcome the problems arising in this cooperation by analyzing the intensity of interregional cooperation between Russia and China in the Volga — Yangtze format.Tasks. To analyze program documents and mass-media materials in terms of coverage of the implementation of Sino-Russian projects in the Volga-Yangtze format. To carry out a quantitative analysis of existing joint projects with China in the Volga Federal District. To identify the “growth points” of further economic cooperation between Russia and China in the Volga — Yangtze format.Methods. Empirical research methods, search and analysis of information from mass media, analysis and comparison of data, comparison and generalization were used in the work.Results. By studying the current state of the economic component of Russian-Chinese cooperation in the Volga — Yangtze format, it was possible to identify the difficulties existing in cooperation between the two sides, which could be purposefully solved if the effectiveness of local cooperation was strengthened.Conclusions. At the present stage, there are some obstacles to the effective development of cooperation between the regions of the Volga Federal District and the territories of the upper and middle reaches of the Yangtze River of the People’s Republic of China in the Volga — Yangtze format, such as difficulties in the macroeconomic situation in Russia, the weakness of the foundation of regional cooperation, the need for an effective coordination mechanism at the regional level, as well as clear schemes of financial and tax support. In addition, based on the geographical features of the regions and the reliance of regional economies on water resources, the development of environmental cooperation in the Volga — Yangtze format would be a progressive format of cooperation.